The development of flip book maker-based e-module in computer applications course for elementary education student teachers - Mislinawati, Mislinawati; Fitriani, Suci (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2023)
The inconsistent implementation of e-modules within the Faculty of Teacher Training and Education (FKIP) at Syiah Kuala University (USK), particularly in the Elementary School Teacher Education (PGSD) program, highlights a crucial gap in adapting to technological advancements. In response to this, the authors identified the need for digital teaching materials aligned with information technology (IT) for effective instruction. This study focuses on the development and evaluation of flip book-based e-modules for the Computer Application course (APLIKOM) within the PGSD program. Utilizing a research and development (R&D) approach, the study employed the ADDIE development model. Initial testing involved a small-scale group of 10 students, while a larger cohort of 30 students participated in subsequent evaluations. Validation from material and media experts produced an impressive average score of 86.5%. Student responses, assessed through both small and large-scale tests, exhibited a commendable average of 89.5%. Evaluation tests demonstrated the effectiveness of the flip book-based e-module, yielding an overall average score of 88. Notably, 100% of students in both test groups met the minimum criteria for mastery learning. The findings suggest that the developed flip book-based e-module for the APLIKOM course is valid, practical, and effective in delivering teaching materials to students. This research contributes valuable insights into the integration of digital tools in teacher education programs, addressing the pressing need for IT-based instructional materials in contemporary educational settings